The BETHY/JSBACH Carbon Cycle Data Assimilation System: experiences and challenges. Issue 4 (9th October 2013) - Kaminski, T.; Knorr, W.; Schürmann, G.; Scholze, M.; Rayner, P. J.; Zaehle, S.; Blessing, S.; Dorigo, W.; Gayler, V.; Giering, R.; Gobron, N.; Grant, J. P.; et al.
<x xml:space="preserve">Abstract</x> [1] We present the concept of the Carbon Cycle Data Assimilation System and describe its evolution over the last two decades from an assimilation system around a simple diagnostic model of the terrestrial biosphere to a system for the calibration and initialization of the land component of a comprehensive Earth system model. We critically review the capability of this modeling framework to integrate multiple data streams, to assess their mutual consistency and with the model, to reduce uncertainties in the simulation of the terrestrial carbon cycle, to provide, in a traceable manner, reanalysis products with documented uncertainty, and to assist the design of the observational network. We highlight some of the challenges we met and experience we gained, give recommendations for operating the system, and suggest directions for future development.